Development of betulinic acid as an agonist of TGR5 receptor using a new in vitro assay - Lo SH (Drug Design, Development and Therapy, 2016)
Shih-Hsiang Lo,1,2 Kai-Chung Cheng,3 Ying-Xiao Li,3,4 Chin-Hong Chang,4,5 Juei-Tang Cheng,4,6 Kung-Shing Lee7,8 1Division of Cardiology, Department of Internal Medicine, Zhongxing Branch of Taipei City Hospital, 2Department of History and Geography, University of Taipei, Taipei, Taiwan; 3Department of Psychosomatic Internal Medicine, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, Japan; 4Department of Medical Research, 5Department of Neurosurgery, Chi-Mei Medical Center, Yong Kang, 6Institute of Medical Science, College of Health Science, Chang Jung Christian University, Tainan, 7Department of Surgery, Pingtung Hospital, 8Division of Neurosurgery, Department of Surgery, Kaohsiung Medical University Chung-Ho Memorial Hospital, School of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan Background: G-protein-coupled bile acid receptor 1, also known as TGR5 is known to be involved in glucose homeostasis. In animal models, treatment with a TGR5 agonist induces incretin secretion to reduce hyperglycemia. Betulinic acid, a triterpenoid present in the leaves of white birch, has been introduced as a selective TGR5 agonist. However, direct activation of TGR5 by betulinic acid has not yet been reported. Methods: Transfection of TGR5 into cultured Chinese hamster ovary (CHO-K1) cells was performed to establish the presence of TGR5. Additionally, TGR5-specific small interfering RNA was employed to silence TGR5 in cells (NCI-H716 cells) that secreted incretins. Uptake of glucose by CHO-K1 cells was evaluated using a fluorescent indicator. Amounts of cyclic adenosine monophosphate and glucagon-like peptide were quantified using enzyme-linked immunosorbent assay kits. Results: Betulinic acid dose-dependently increases glucose uptake by CHO-K1 cells transfected with TGR5 only, which can be considered an alternative method instead of radioligand binding assay. Additionally, signals coupled to TGR5 activation are also increased by betulinic acid in cells transfected with TGR5. In NCI-H716 cells, which endogenously express TGR5, betulinic acid induces glucagon-like peptide secretion via increasing calcium levels. However, the actions of betulinic acid were markedly reduced in NCI-H716 cells that received TGR5-silencing treatment. Therefore, the present study demonstrates the activation of TGR5 by betulinic acid for the first time. Conclusion: Similar to the positive control lithocholic acid, which is the established agonist of TGR5, betulinic acid has been characterized as a useful agonist of TGR5 and can be used to activate TGR5 in the future. Keywords: CHO-K1 cell, lithocholic acid, NCI-H716 cell, transfection, siRNA